Pengaruh Substitusi Tepung Tulang Ikan Lele (Clarias batrachus) Terhadap Kadar Kalsium, Kekerasan dan Daya Terima Biskuit - Mahmudah, Siti, Rusdin Rauf, S.TP., M.P, Fitriana Mustikaningrum, S.Gz, M.Sc (2013)
Background: The Osteoporosis cases in Indonesia is quite high. This is caused by inadequate intake of calcium through food. Catfish bone flour can be used as a substituent of wheat flour in making biscuits. Purpose: The purpose of this study was to determine the effect of substitution catfish bone flour on calcium content, hardness and acceptability of biscuits. Method: The completely randomized design was used in the research with 4 treatments substitution of catfish bone flour were 0%, 10%, 20%, and 30%. Data were analyzed using the one way anova, followed by Duncan at significance level of 95%. Result: The results showed that the catfish bone flour indicated the moisture content 11.34%, ash content 59.49%, protein content 23.86%, fat content 0.96%, carbohydrate 4.35% and calcium level 17.47%. There was effect of bone flour substitution on calcium levels of biscuits. The more the substitution of catfish bone flour, the more the calcium contents of biscuits. The highest calcium level of biscuit was given by substitution 30% (10,15% calcium). The hardness of biscuit was affected by the substitution of catfish bone flour. The substitution 10% gave the biggest hardness of biscuits. Biscuit with substitution 0% and 20% were the most preferred by panelists. Suggestion : Based on acceptability of biscuits, to substitute 20% catfish bone flour in biscuit